Meningkatkan Konsentrasi Belajar Anak melalui Olahraga Memanah di TK IT Permata Al-Maidah Koja Jakarta Utara - Imran, Ali; Susanti, Robiah (Prodi PIAUD Fakultas Tarbiyah Insitut PTIQ Jakarta, 2024)
The Archery Sports Method is one of the learning methods that can increase children's learning concentration, because concentration has a very important role in children's learning, so that children's learning is not boring, along with technological developments, new technology has given birth, such as gadgets, which have an impact on children's lack of concentration in learning. , the archery sport method can divert children's attention so they don't always play with gadgets. So learning with Archery sports methods in early childhood are not boring. This research aims to: 1) develop children's learning concentration abilities; 2) providing fun learning through the archery sport method in group B TKIT Permata Al-Maidah. The research method was carried out using classroom actions. The research subjects were students from group B1 at TKIT Permata Al-Maidah, consisting of 15 children, in Koja District, North Jakarta. The data analysis technique used was percentage descriptive and descriptive of students' activities. The results of the research show that the children's ability to concentrate achieved by students in the B1 TKIT Permata Al-Maidah group has increased compared to before where the development of children's concentration was onlyreached 50%, but after carrying out classroom action research practice using the storytelling method using audio-visual media, in the first cycle there was an increase reaching 75%, therefore re-research was carried out so that in the second cycle the increase reached 85%, where the level of achievement was already meet the research target of 85%. Likewise, it is easier for teachers to convey archery sports methods, and provide fun learning.